EKSPLORASI LIMBAH ORGANIK DAN PENGOLAHANNYA SEBAGAI BAHAN PAKAN IKAN - Yuli - Andriani; M. Galuh - Nurdaya; Rusky Intan Pratama; Iskandar - -; M. Fatah - Wiyatna (JURNAL PERIKANAN DAN KELAUTAN, 2024)
Organic waste production is currently very abundant, but its handling is still a significant problem, especially related to environmental pollution. One of the innovations that can be applied to overcome this problem is the manufacture of alternative feeds from various kinds of organic waste. Organic waste has great potential to be utilized as fish feed, which can reduce dependence on commercial feed. The use of various types of organic wastes as raw materials for fish farm feed can not only save production costs, but also help reduce the volume of organic waste, which in turn supports better environmental management. Some of the local feed raw materials that have potential as alternative feeds come from human food waste and agricultural industries. Artificial feeding in intensive fish farming is necessary to support optimal fish growth. However, the use of artificial feed or pellets tends to incur relatively high costs. Therefore, alternative raw materials are needed as a solution to reduce feed costs.